Molecular Approach to Electrochemically Switchable Monolayer MoS2 Transistors - Zhao, Yuda; Bertolazzi, Simone; Maglione, Maria Serena; Rovira, Concepció; Mas‐Torrent, Marta; Samorì, Paolo (Advanced materials (Weinheim), 2020)
As Moore's law is running to its physical limit, tomorrow's electronic systems can be leveraged to a higher value by integrating “More than Moore” technologies into CMOS digital circuits. The hybrid heterostructure composed of two‐dimensional (2D) semiconductors and molecular materials represents a powerful strategy to confer new properties to the former components, realize stimuli‐responsive functional devices, and enable diversification in “More than Moore” technologies. Here, an ionic liquid (IL) gated 2D MoS2 field‐effect transistor (FET) with molecular functionalization is fabricated. The suitably designed ferrocene‐substituted alkanethiol molecules not only improve the FET performance, but also show reversible electrochemical switching on the surface of MoS2. Field‐effect mobility of monolayer MoS2 reaches values as high as ≈116 cm2 V−1 s−1 with Ion/Ioff ratio exceeding 105. Molecules in their neutral or charged state impose distinct doping effect, efficiently tuning the electron density in monolayer MoS2. It is noteworthy that the joint doping effect from IL and switchable molecules results in the steep subthreshold swing of MoS2 FET in the backward sweep. These results demonstrate that the device architecture represents an unprecedented and powerful strategy to fabricate switchable 2D FET with a chemically programmed electrochemical signal as a remote control, paving the road toward novel functional devices. An ionic‐liquid‐gated two‐dimensional MoS2 field‐effect transistor with the functionalization of ferrocene‐substituted alkanethiol molecules is fabricated. It can in situ program and sense the electrochemical state of adsorbed redox‐active molecules. The electrochemical stimuli from the redox‐active molecules represent a remote control to modulate the electrical transport of monolayer MoS2.